Implementation of Debate Learning Strategy to Improve Students' English Speaking Skills at SMA Negeri 1 Kuta Baro - Mukminin, Teuku Fahrul; Muliasari (DEEP LEARNING: Journal of Educational Research, 2025)
Speaking skills are a crucial component of English language acquisition, yet many eleventh-grade students at SMA Negeri 1 Kuta Baro still face challenges in fluency, confidence, and argumentation skills. This study aims to test the effectiveness and analyze the process of improving students' speaking skills through the implementation of the Debate Learning Strategy. This study used a Classroom Action Research (CAR) design implemented in two cycles, each consisting of planning, action, observation, and reflection. The subjects were all eleventh-grade students at SMA Negeri 1 Kuta Baro. Data were collected through speaking practice performance tests (pre-test and post-test per cycle) and observation sheets. The results showed a significant improvement in students' speaking skills after implementing the Debate Learning Strategy. Initially, students' average scores were in the low category. After Cycle I, the average score increased, and after Cycle II, with improvements, the average score increased significantly, reaching the school's learning completion target. This improvement is reflected not only in linguistic aspects (accuracy and fluency), but also in non-linguistic aspects, namely students' confidence and activeness in presenting arguments and responding to their interlocutors. Thus, it can be concluded that the Debate Learning Strategy has proven effective as a learning innovation that successfully improved the English speaking skills of 11th-grade students at SMA Negeri 1 Kuta Baro. This strategy is recommended for implementation to create a more interactive and challenging learning environment.